2018
DOI: 10.3171/2016.11.jns16715
|View full text |Cite
|
Sign up to set email alerts
|

Deep brain stimulation for Parkinson’s disease: meta-analysis of results of randomized trials at varying lengths of follow-up

Abstract: OBJECTIVE Deep brain stimulation (DBS) is effective in the management of patients with advanced Parkinson's disease (PD). While both the globus pallidus pars interna (GPi) and the subthalamic nucleus (STN) are accepted targets, their relative efficacy in randomized controlled trials (RCTs) has not been established beyond 12 months. The objective of this study was to conduct a meta-analysis of RCTs to compare outcomes among adults with PD undergoing DBS of GPi or STN at various time points, including 36 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(79 citation statements)
references
References 57 publications
(104 reference statements)
2
76
0
1
Order By: Relevance
“…Findings have been reported in [17]. 2 This patient was operated in the GPi, and therefore the results were reported separately in [39] 3,4 These randomisation orders belong to the same patient (PD01). As this patient had to be measured unilaterally in both hemispheres, due to a defect in one of the aDBS box channels, each hemisphere was assigned to a different randomisation order.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings have been reported in [17]. 2 This patient was operated in the GPi, and therefore the results were reported separately in [39] 3,4 These randomisation orders belong to the same patient (PD01). As this patient had to be measured unilaterally in both hemispheres, due to a defect in one of the aDBS box channels, each hemisphere was assigned to a different randomisation order.…”
Section: Resultsmentioning
confidence: 99%
“…These include incomplete symptom suppression and side effects, such as stimulation-induced dysarthria (SID), and dyskinesias. In addition to this, most of the studies have documented the benefits of DBS only up to three years after implantation [2]. A handful of studies that have followed DBS patients in the long term (5-10 years after implantation) have suggested that the efficacy of DBS may reduce over time, especially in bradykinesia items [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Based on long‐term follow‐up, patients treated with STN DBS still have significant improvement in PD cardinal features and reduced motor fluctuation and levodopa‐induced dyskinesia (LID) at 10 years after surgery . Although bilateral GPi DBS may have more variable long‐term results, significant improvement was maintained for up to 5 years …”
Section: Invasive Brain Stimulation In Pd Dbsmentioning
confidence: 99%
“…7 Although bilateral GPi DBS may have more variable long-term results, significant improvement was maintained for up to 5 years. 8 GPi DBS is usually considered as effective as STN DBS for treatment of PD cardinal symptoms. 5 A recent meta-analysis concluded that GPi and STN DBS provide equivalent tremor suppression.…”
Section: Invasive Brain Stimulation In Pd Dbs Subthalamic Nucleus Andmentioning
confidence: 99%
“…Deep brain stimulation (DBS) has been established as an effective therapy for movement disorders such as essential tremor (ET) and Parkinson's disease (PD) over the past decades . Traditionally, DBS uses 120–185 Hz pulses via a lead implanted in a target brain structure, such as the subthalamic nucleus (STN).…”
Section: Introductionmentioning
confidence: 99%